Direct thiophenylation accompanying orthoester-cleavage of 1, 2, 4-O-orthoacetyl-3, 6-O-(o-xylylene)glucopyranose. (30th January 2015) - Uchino, Takuya; Tomabechi, Yusuke; Fukumoto, Atsushi; Yamada, Hidetoshi
Graphical abstract: Highlights: A phenylthioglucoside that conformation was locked to an axial-rich form was synthesized. A direct thiophenylation of 3, 6- O -( o -xylylene) bridged 1, 2, 4- O -orthoacetylglucose was established. The method reduced the synthetic step for production of the corresponding fluoride. Abstract: The 3, 6- O -( o -xylylene) bridge locks the conformation of glucopyranose to an axial-rich form. Although the conformational lock induces complete β-selectivity in a glycosylation reaction, the leaving group of the glycosyl donor is limited to fluorine. On the other hand, the bridge confers the furanose-preferred property to glucose, which makes synthesis of corresponding pyranosyl derivatives that equip various leaving groups difficult. This problem was solved through direct phenylthio glucosidation of 3, 6- O -( o -xylylene)-1, 2, 4- O -orthoacetylglucose accompanying cleavage of the orthoester moiety. This paper describes the process of establishing direct thiophenylation. This process reduced the synthetic steps for the known glucopyranosyl fluoride and will expand application of conformationally locked glycosyl donors.